2018
DOI: 10.1093/brain/awy242
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for peri-ictal blood–brain barrier dysfunction in patients with epilepsy

Abstract: Epilepsy has been associated with a dysfunction of the blood-brain barrier. While there is ample evidence that a dysfunction of the blood-brain barrier contributes to epileptogenesis, blood-brain barrier dysfunction as a consequence of single epileptic seizures has not been systematically investigated. We hypothesized that blood-brain barrier dysfunction is temporally and anatomically associated with epileptic seizures in patients and used a newly-established quantitative MRI protocol to test our hypothesis. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
77
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(80 citation statements)
references
References 54 publications
3
77
0
Order By: Relevance
“…There is a clear association between epilepsy and BBB dysfunction. BBB leakage in epilepsy patients is visible with contrast-enhanced MRI (Horowitz et al, 1992; Alvarez et al, 2010; Rüber et al, 2018; Fig. 2 I), and analysis of brain tissue from epileptic patients shows increased parenchymal albumin (Cornford et al, 1998a; Mihály and Bozóky, 1984), implicating blood-to-brain extravasation of large molecules.…”
Section: Bbb Dysfunctionmentioning
confidence: 99%
“…There is a clear association between epilepsy and BBB dysfunction. BBB leakage in epilepsy patients is visible with contrast-enhanced MRI (Horowitz et al, 1992; Alvarez et al, 2010; Rüber et al, 2018; Fig. 2 I), and analysis of brain tissue from epileptic patients shows increased parenchymal albumin (Cornford et al, 1998a; Mihály and Bozóky, 1984), implicating blood-to-brain extravasation of large molecules.…”
Section: Bbb Dysfunctionmentioning
confidence: 99%
“…The mechanisms underlying seizure-induced BBB alterations are not fully understood. The relatively rapid increase in permeability during seizures (within~30 min), together with a more lasting effect (for hours) [35] suggest multiple mechanisms act in concert to alter BBB properties. For example, seizure-induced increases in brain glutamate levels may lead to barrier dysfunction [21,36].…”
Section: Why Do Epileptogenic Brain Insults and Seizures Alter The Momentioning
confidence: 99%
“…Human MRI studies using contrast agents have shown that epilepsy-causing brain injuries are associated with temporal and anatomical BBB dysfunction ( 21 ), and BBB disruption can occur after seizures ( 29 ). To provide a clinical context to our animal model findings, we analysed contrast-enhanced MRI brain imaging studies of a set of three patients who recently experienced seizures (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…While prolonged or repeated seizures are known to cause disruption of the BBB, the focus until now has been on understanding how this contributes to epilepsy ( 20, 29 ). Here we asked whether BBB disruption after status epilepticus could be appropriated to deliver a systemically-administered antagomir to treat epilepsy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation